Analysis of The Influence of Work Motivation on Employee Performance at PT Pertamina EP CEPU (PEPC) Regional 4 - Herman, Herman; Suganda, Erik Irawan; Oktavia, Nanda Diena (Jurnal Manajemen (Edisi Elektronik), 2025)
This research aims to analyze the influence of work motivation on employee performance at PT Pertamina Ep Cepu (PEPC) Regional 4 Function Supply Chain Management. The type of research used is quantitative research with descriptive analysis methods. Data collection techniques were obtained from observation and questionnaires. The samples used in this research were 40 samples using the sampling method, namely census. The analytical method used is descriptive analysis, simple linear regression, with the testing conditions namely hypothesis testing where there are several testing stages, namely the partial test (t) and the coefficient of determination test (R2). The results of the hypothesis test state that the influence of work motivation on employee performance shows significant results and has a positive sign. Based on a value of 4.216 greater than 2.026 or a value > 4.216 > 2.026 then  H_0 is rejected and Ha is accepted. The Functional Relationship between the influence of work motivation on employee performance is Y = 14.368 + 0.567, with a regression coefficient of r = 0.565 and a coefficient of determination R Square = 0.319. So these results show that work motivation as a variable (X) has a positive and significant effect on employee performance, namely the variable (Y). The large value of the coefficient of determination shows that the independent variable, namely work motivation (X), can explain the dependent variable, namely employee performance (Y), by 31.9%, while the remaining 69.1% is explained by other variables not included in this research model.